Comparison of Clavicular Hook Plate Outcome With and Without Coracoclavicular Suture Fixation in Patients With Acute Acromioclavicular Joint Dislocation - Younis, Moaz; Khan, Ghulam Qadir; Shakeel, Imran (Biological and Clinical Sciences Research Journal, 2025)
High-grade acromioclavicular joint (ACJ) dislocations commonly require surgical stabilization. Clavicular hook plate fixation is widely used in low-resource settings; however, whether additional coracoclavicular (CC) ligament augmentation provides incremental clinical benefit remains uncertain. Objective: To compare functional and radiographic outcomes of clavicular hook plate fixation with and without CC suture augmentation in adults with acute ACJ dislocation. Methods: This single-center randomized controlled trial was conducted at the Department of Orthopedic Surgery, Nishtar Hospital, Multan, from February to August 2025. Sixty adults (18–60 years) with acute ACJ dislocation (<7 days) were randomized into two groups: hook plate fixation with CC suture augmentation (Group A, n = 30) and hook plate fixation alone (Group B, n = 30). The primary outcome was functional recovery assessed at three months using the American Shoulder and Elbow Surgeons (ASES) score. The secondary outcome was radiographic maintenance of reduction, measured using the coracoclavicular distance discrepancy ratio (CCDR). Operative time was also compared. Independent sample t-tests were used for between-group comparisons. Results: Baseline demographic and clinical characteristics were comparable between groups. The mean ASES score at three months was significantly higher in Group A compared with Group B (90.8 ± 4.1 vs 83.6 ± 5.0; p < 0.001). Radiographic assessment demonstrated significantly better maintenance of reduction in Group A, with lower CCDR values (108.4 ± 12.3 vs 124.7 ± 15.6; p < 0.001). Operative duration was slightly longer in the augmented group but did not differ significantly between groups (58.6 ± 8.9 vs 52.4 ± 7.6 minutes; p = 0.08). Stratified analyses showed consistent functional benefits of CC augmentation across age, gender, body mass index, and duration of dislocation. Conclusion: Coracoclavicular suture augmentation in addition to clavicular hook plate fixation results in superior short-term functional outcomes and improved radiographic maintenance of reduction in patients with acute ACJ dislocation, without a significant increase in operative time.